Effectiveness Of Training Using Booklets On The Knowledge And Attitude Of Cadres In Accompanying Complementary Feeding For Stunted Toddlers Aged 12–59 Months (A Study Of Satellite Posyandu Cadre Assis - Sri Achadi Nugraheni; Merisha Dhea Salisa; Laksmi Widajanti; Mohammad Zen Rahfiludin; Apoina Kartini (Journal of Social Research, 2025)
Stunting in toddlers remains a critical public health issue that affects physical growth, cognitive development, and overall well-being. This study aims to analyze the effectiveness of training using booklets on the knowledge and attitudes of Posyandu Satellite cadres in accompanying complementary feeding for stunted toddlers aged 12–59 months in the working area of Lamper Tengah Health Center, Semarang. A quantitative research design with a quasi-experimental nonequivalent control group approach was employed, involving 44 cadres divided into intervention and control groups. Data were collected through pre-test and post-test questionnaires, focusing on knowledge and attitude variables. The results showed a significant improvement in the knowledge level of the cadres after training, with respondents in the “good” knowledge category increasing from 72.7% to 86.4%. Similarly, the attitude of cadres improved, with those in the “positive” attitude category increasing from 22.7% to 68.2% after the intervention. Statistical analysis using paired t-tests and Wilcoxon tests confirmed a significant difference (p < 0.05) between pre-test and post-test scores for both knowledge and attitudes. The use of booklets proved to be an effective and practical educational tool, providing structured and easy-to-understand information that enhanced the cadres’ capacity to support complementary feeding practices for stunted toddlers.